The IMF Financial Surveillance Strategy. (Policy Papers; Policy Paper ;, 2012)
This paper outlines strategic priorities for the IMF's financial surveillance in the coming years. It complements recent discussions on the work agenda in this area. It takes stock of innovations and gaps in financial surveillance by the Fund during the past decade, including in the wake of the current global financial crisis. It proposes concrete and prioritized steps to further strengthen financial surveillance so that the Fund can fulfill its mandate to ensure the effective operation of the international monetary system and support global economic and financial stability.